A critical review of cement composites containing recycled aggregates with graphene oxide nanomaterials. (15th June 2023) - Alvi, Ishrat Hameed; Li, Qi; Hou, Yunlu; Onyekwena, Chikezie Chimere; Zhang, Min; Ghaffar, Abdul
Abstract: Construction and demolition waste (CDW) constitute an environmental burden. Various strategies have been developed to reutilize these wastes by converting them to recycled aggregates (RA), but some limitations exist, such as low mechanical performance and durability issues. Recent research on graphene oxide (GO) admixed cement composites has studied the transformation of conventional cementitious materials into durable composites. However, the role of GO in improving the performance of RA-based cement composites remains critically unexplored. The synergy between GO and RA in cement composites is a new technique for producing environment-friendly sustainable construction materials. This comprehensive review aims to evaluate the research efforts on utilizing GO in RA-based cement composites and map the research viewpoints from available literature (by bibliometric and keyword analyses). Data from published articles were summarized to assess the impact of various GO contents on RA-based cement composites (GO-RA-CC). By analyzing the merits and demerits of GO, the article highlights the recent evolutions of GO-RA-CC for various construction applications. After analyzing the keyword occurrences, the impact of varying GO content on the mechanical and durability properties of GO-RA-CC is selected for appraisal. The mechanism behind the properties' enhancement of the recycled aggregate concrete system by GO is mainly contributed by improved interfacial transition zones and increased hydration reactions. Further, the life cycle assessment studies on GO-RA-CC showed better environmental performance, particularly in CO2 emissions reduction, than conventional cement composites. Concluding remarks highlight the challenges and future perspectives of using GO as a nano-filler material to resolve the crack propagation and high porosity of RA-CC, focusing on the environmental impact of the material. Graphical abstract: Image 1 Highlights: Graphene oxide (GO) can potentially recycle construction and demolition waste. GO improves the properties of cement composites made from recycled aggregates (RA). GO helps increase the percentage of recycled aggregates in composites. The composite containing RA and GO emits less CO2 than a standard composite.